Perancangan Sistem Penentuan Harga Pokok Produksi Pada UKM Accura Production Jambi - Novia Kurniasih; Rezagi Meilano (Journal of Applied Accounting And Business, 2020)
Accura Production is a small or medium enterprise (SME) engaged in printing, digital printing and convection. This company determines the selling price of products based on estimates, so the selling price of the product may be too high or low because currently the cost of goods calculation does not cover all cost elements incurred in production costs. The purpose of this research is to design a system for determining the cost of goods manufactured in accordance with cost accounting standards. The data collection method was done by interview, observation and literature study. The data analysis technique uses the Waterfall system development method and the determination of the cost of production uses the full costing method. Programming language using PHP and database using MySQL, and system design using DFD. The result of this research is that there is a system currently being developed which is useful to reduce the occurrence of production cost calculation errors because the system designed will display all elements of production costs so that it is monitored more quickly, accurately, and in detail.